HUBUNGAN ASUPAN KALORI, AKTIVITAS FISIK, PERILAKU SEDENTARI, DAN ADIKSI SMARTPHONE DENGAN KEJADIAN OVERWEIGHT PADA REMAJA DI SMAN 3 RANGKASBITUNG - Shinta, Rei; Fitriani, Anna (UHAMKA PRESS, 2024)
Overweight is a condition of a person's weight that exceeds normal weight, which is caused by excess fat accumulation. Some factors that can cause overweight are excess calorie intake, low physical activity, high sedentary behavior, and smartphone addiction. The purpose of the study was to see the relationship between calorie intake, physical activity, sedentary patterns, and smartphone addiction to the incidence of overweight in adolescents at SMAN 3 Rangkasbitung. This type of research used a cross-sectional research design. The research subjects amounted to 92 students at SMAN 3 Rangkasbitung. Overweight data was taken by anthropometric measurements of body weight and height. The calory intake data in this research was obtained through interviews with food recall questionnaires 2x24 hours, data physical activity with Global Physical Activity Questionnaire (GPAQ), sedentary patterns with Adolescent Sedentary Activity Questionnaire (ASAQ), and smartphone addiction data with Smartphone Addiction Scale short version questionnaire (SAS SV). The types of data analysis used are univariate and bivariate. Results from bivariate analysis using chi-square showed a significant relationship between calorie intake with overweight, physical activity with overweight, sedentary behavior with overweight, smartphone addiction with overweight, and smartphones addiction with sedentary behavior. Calorie intake, physical activity, sedentary behavior, and smartphone addiction are related to the incidence of overweight and smartphone addiction is related to sedentary behavior.